FRN and P300 ERP effect modulation in response to feedback sensitivity: The contribution of punishment-reward system (BIS/BAS) and Behaviour Identification of action - Michela Balconi; Davide Crivelli (2009)
Disruption of the sense of being effective and causally determinant in performing an action was explored in the present research by inducing an erroneous external spatial feedback in response to the subject's behaviour. ERPs were recorded from fifteen subjects when they were receiving mismatching/matching feedback information on direction. In addition, subjective sensitivity to the external cues was monitored by Behavioural Inhibition System (BIS) and Behavioural Activation System (BAS) measures, as well as Behaviour Identification process was tested by Behavior Identification Form (BIF). One negative ERP deflections of higher amplitude was revealed in concomitance to false feedback, peaking at about 210ms post-stimulus, more central-posteriorly localized. We supposed that it may represent feedback-error system of which activity might be reflected in FRN, deputed to monitor the unattended feedback furnished by an external system. Moreover, a P3b effect was also observed in great measure for false spatial feedback, more posteriorly (Pz) distributed. According to the context-updating hypothesis, the P3b may reflect the revision of the mental model of the context. BIS showed to be more sensitive to both veridical and false feedback that increased FRN, whereas higher-BAS and BAS-Reward measures revealed an increased proactive attitude to external feedback (higher P3b). Finally, low-level of action representation explained FRN amplitude more than high-level one.